2017
DOI: 10.1038/nm.4334
|View full text |Cite
|
Sign up to set email alerts
|

Tmbim1 is a multivesicular body regulator that protects against non-alcoholic fatty liver disease in mice and monkeys by targeting the lysosomal degradation of Tlr4

Abstract: Non-alcoholic steatohepatitis (NASH) is an increasingly prevalent liver pathology that can progress from non-alcoholic fatty liver disease (NAFLD), and it is a leading cause of cirrhosis and hepatocellular carcinoma. There is currently no pharmacological therapy for NASH. Defective lysosome-mediated protein degradation is a key process that underlies steatohepatitis and a well-recognized drug target in a variety of diseases; however, whether it can serve as a therapeutic target for NAFLD and NASH remains unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
105
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 75 publications
4
105
2
Order By: Relevance
“…Insulin resistance and inflammation are vital parts in the development of hepatic steatosis . USP18‐HTG mice exhibited decreased fasting blood glucose and insulin levels in contrast with their control littermates fed HFD (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Insulin resistance and inflammation are vital parts in the development of hepatic steatosis . USP18‐HTG mice exhibited decreased fasting blood glucose and insulin levels in contrast with their control littermates fed HFD (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…H,J). Previous studies demonstrated that in obese individuals, Iκ kinase β (IKKβ)‐mediated activation of NF‐κB by nutritional overload triggers hepatic inflammatory reaction . We thus further investigated whether USP4 mediated the IKKβ/NF‐κB signaling pathway during HFD‐induced related pathologies.…”
Section: Resultsmentioning
confidence: 99%
“…Randomization and blinding strategies were used whenever possible. Animal cohort sizes were determined on the basis of similar previous studies …”
Section: Methodsmentioning
confidence: 99%